2021
DOI: 10.1108/lodj-07-2020-0284
|View full text |Cite
|
Sign up to set email alerts
|

Crisis leadership from the perspective of employees during the COVID-19 pandemic

Abstract: PurposeThe purpose of the paper is to identify traits and behaviors of organization leaders that were deemed helpful by employees during the COVID-19 pandemic.Design/methodology/approachThis is an exploratory qualitative study that utilized online surveys. Data from 155 participants were subjected to content analysis.FindingsSeveral interrelated traits and behaviors of effective crisis leadership were identified. These were clustered into three superordinate themes – attending to the person, taking charge and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 46 publications
7
56
0
Order By: Relevance
“…What is effective during "normal" conditions, may be less effective in times of crisis (James et al, 2011). Studies have suggested that during times of crisis, individuals might favor decisive efforts (Caringal-Go et al, 2021;James et al, 2011;Lin et al, 2021). This, combined with our findings, suggests that transformational leadership behaviors that emphasize sharing the group's future vision and challenging current ways of thinking might decrease certainty and be less effective during a time of uncertainty and stress.…”
Section: Theoretical Implicationssupporting
confidence: 52%
See 3 more Smart Citations
“…What is effective during "normal" conditions, may be less effective in times of crisis (James et al, 2011). Studies have suggested that during times of crisis, individuals might favor decisive efforts (Caringal-Go et al, 2021;James et al, 2011;Lin et al, 2021). This, combined with our findings, suggests that transformational leadership behaviors that emphasize sharing the group's future vision and challenging current ways of thinking might decrease certainty and be less effective during a time of uncertainty and stress.…”
Section: Theoretical Implicationssupporting
confidence: 52%
“…Organizations do not operate within a vacuum, but rather exist in a volatile and complex environment (Williams et al, 2019) and extreme contexts arguably elicit the greatest need for effective leadership (Caringal-Go et al, 2021;Geier, 2016;Hannah et al, 2009). The results of the current study suggest that leadership training might focus on individualized and immediate needs (for support and performance) addressed by transformational leadership behaviors when training supervisors to manage employee well-being in an extreme context.…”
Section: Practical Implicationsmentioning
confidence: 84%
See 2 more Smart Citations
“…Competency theorists commonly group leadership behaviors into task-related competencies, relational competencies, and change and adaptive competencies (Heifetz & Linsky, 2017;Stogdill, 1974;Yukl, 2012). Crisis leadership scholars suggest in addition to the above leadership competencies that are formed and developed outside of crisis situations, collaboration is an important element in the crisis situation (Bavik et al, 2021;Caringal-Go et al, 2021;Kapucu & Ustun, 2018). Figure 1 shows the integrated framework for pandemic leadership that guided our work.…”
Section: Conceptual Modelmentioning
confidence: 99%